Analisis Kinerja Badan Usaha Milik Desa (BUMDes) dalam Pengelolaan Aset Desa di Desa Putat Lor Kecamatan Menganti Kabupaten Gresik - Musyafak, Faris; Sukarno, Sukarno (Universitas 17 Agustus 1945 Surabaya, 2019)
In accordance with Law No. 6 of 2014 Concerning Village in Chapter X Article 87-90 concerning BUMDes in Managing Village Assets. In this study using descriptive qualitatife research type. There were several informants who provided related information in this study, including: Village Head of Putat Lor Village, Chair of BUMDes along with Members, Sports Field Managers and Commercial Tenants. Data collection techniques used were interview observation and documentation. From the results of this study, it is known that concerning BUMDes in managing Village Assets has not significantly affected the economic development of Putat Lor and surrounding communities because BUMDes are just beginning formed and established so that performance carried out has not had a maximum impact on the management and development of Village Assets. The results of this study are related to Performance Analysis according to Dharma which has 3 indicators, namely: Quantity, Quality and Timliness. Keyword: Performance Analysis, BUMDes, Village AssetsÂ